HUMAN BODY- top ten (Macaw Books INDIA, 2013)
Facts and More is a comprehensive guide to the world around us. The ten-book series contains essential information, facts, and more about the Earth, Universe, Human Body, Transportation, Sea Animals, Wild Animals, Birds, Science, Plants and Wonders of the World. The elegant layout presents information and data in an easy format complete with illustrations and lively images